The feeding of children from one to five years (London : His Majesty's Stationery Office)
1942-03 1942 1940s 24 pages 4 1½ oz. meat, 2 oz. fish, or 1 oz. liver or kidney (raw weights), or more if the children like them, and mincing should be gradually stopped. Tripe is also a useful offal, especially for younger children. DRIED MILK It is now necessary to register for supplies of liquid milk. There may not be enough for all the purposes for which it was used in peace-time but dried skimmed milk is an excellent food and contains a very high concentration of valuable nutrients which are practically identical with those of liquid skimmed milk, the nutritive value of which can best be summed up in the words of the Advisory Committee on Nutrition: (First Report 1937, Para- 65, H.M.S.O.) "...skimmed milk stands next to whole milk in the order of nutritive value of foods and differs from the latter only in so far as it contains very little of the fat with its attendant vitamins A and D. Except for these three nutrients, skimmed milk contains all those present in whole milk, or, in other words, all the remaining materials required for the nutrition of the body, viz., the protein, carbohydrate, vitamins B, C and E, and inorganic elements. As with whole milk, however, a statement of the chemical constituents of skimmed milk gives an imperfect idea of its nutritive properties because it leaves unmentioned nutritionally important physio-chemical and biological characteristics.” Dried skimmed milk can be used instead of liquid milk for all forms of cookery ; in hot beverages such as coffee, cocoa, tea; in soups, sauces, salad dressings, puddings, pies and cakes. It should be stored in a dry cool place in a closed container. In these conditions it should keep for some weeks. It can be reconstituted into liquid milk and mixes freely with flour. It should be mixed or reconstituted as required, and after reconstitution it behaves like fresh liquid milk and should be treated with the same care. To prepare liquid skimmed milk: To 3 tablespoons (2 ozs.) of dried milk add two tablespoons of water and beat very hard with a wooden spoon or whisk until smooth. Add one pint of water gradually and stir or whisk well. Alternatively, measure the cold water into a vessel. Sprinkle a little powder on the surface little by little and beat vigorously with a fork or whisk. For special recipes see “Food from Overseas,” H.M.S.O. price 3d. GENERAL NOTES FOR DAILY MEALS. Some suggestions for daily meals and the times when they might be served are given below. It is important to have a good interval between each meal. If meals are crowded digestion may be upset. Orange or tomato juice, swede juice, blackcurrant juice or rose hip syrup to supply vitamin C, and cod liver oil or vitaminised oil, for vitamins A and D, may be given after any meal. It may be found desirable to give a drink of milk, or cocoa made with milk, about 10.30 a.m. Breakfast—8 to 8.30 a.m. Daily, ⅓ pint milk, including that used for porridge. Toast or rusk with butter or margarine, or with yeast extract occasionally. Porridge, egg, fried bread, or bacon or stewed fruit. 127/NU/5/5/1/28